Hydrous cobalt–iridium oxide two-dimensional nanoframes: insights into activity and stability of bimetallic acidic oxygen evolution electrocatalysts. Issue 7 (24th February 2021) - Ying, Yuanfang; Godínez Salomón, Jose Fernando; Lartundo-Rojas, Luis; Moreno, Ashley; Meyer, Robert; Damin, Craig A.; Rhodes, Christopher P.
Abstract : Hydrous cobalt–iridium oxide two-dimensional nanoframes consist of interconnected Co–Ir alloy domains within an unsupported, carbon-free, porous nanostructure and exhibit a higher oxygen evolution activity and similar stability compared to IrO2 . Abstract : Acidic oxygen evolution reaction (OER) electrocatalysts that have high activity, extended durability, and lower costs are needed to further the development and wide-scale adoption of proton-exchange membrane electrolyzers. In this work, we report hydrous cobalt–iridium oxide two-dimensional (2D) nanoframes exhibit higher oxygen evolution activity and similar stability compared with commercial IrO2 ; however, the bimetallic Co–Ir catalyst undergoes a significantly different degradation process compared with the monometallic IrO2 catalyst. The bimetallic Co–Ir 2D nanoframes consist of interconnected Co–Ir alloy domains within an unsupported, carbon-free, porous nanostructure that allows three-dimensional molecular access to the catalytically active surface sites. After electrochemical conditioning within the OER potential range, the predominately bimetallic alloy surface transforms to an oxide/hydroxide surface. Oxygen evolution activities determined using a rotating disk electrode configuration show that the hydrous Co–Ir oxide nanoframes provide 17 times higher OER mass activity and 18 times higher specific activity compared to commercial IrO2 . The higher OER activities of the hydrous Co–Ir nanoframes are attributed to the presence of highly active surface iridium hydroxide groups. The accelerated durability testing of IrO2 resulted in lowering of the specific activity and partial dissolution of Ir. In contrast, the durability testing of hydrous Co–Ir oxide nanoframes resulted in the combination of a higher Ir dissolution rate, an increase in the relative contribution of surface iridium hydroxide groups and an increase in specific activity. The understanding of the differences in degradation processes between bimetallic and monometallic catalysts furthers our ability to design high activity and stability acidic OER electrocatalysts.